Infrastructure Development to Support Tourist Attractions in Citeureup District (Case Study: Hambalang Village and Tajur Village) - Hijarulloh Hijarulloh; Umar Mansyur (Publikasi Indonesia, 2024)
The supporting infrastructure for tourism in Hambalang Village and Tajur Village is still inadequate. This is evident from the lack of adequate tourist facilities and infrastructure, such as roads, parking lots, toilets, and other public facilities. The objectives of this research are: (1) To identify the distribution of tourist attractions and their potential to become prominent tourist destinations in Hambalang Village and Tajur Village, Citeureup District, and (2) To determine the needs for supporting tourism infrastructure in Hambalang Village and Tajur Village, Citeureup District. This research uses Likert data analysis techniques, descriptive analysis, and the miz method to achieve these objectives. The research results show that all tourist attractions in Hambalang and Tajur Villages have the highest potential for natural physical tourist attractions, with Agrowisata Villa Hambalang (2.25) ranking the highest. Based on the potential for artificial physical attractions, the highest scores are 129 Resto & Coffee (2.53). The infrastructure prioritized for development in Hambalang Village based on the IPA analysis results are: (1) Signposts or directions, (2) Gazebos (shelters), and (3) Individual/family seating areas. Meanwhile, the infrastructure prioritized for development in Tajur Village based on the IPA analysis results are: (1) Provision of road networks, (2) Signposts or directions, (3) Eating places, (4) Provision of electricity networks, (5) Provision of clean water networks, and (6) Provision of telecommunication networks. With the right infrastructure development, the tourism potential in Hambalang and Tajur Villages can be optimized, thus attracting more tourists and boosting the local economy.